The circular economy: historical grounds - Cardoso, José Luís (2018)
The circular economy has come to stay. There can be no doubt about this: all one has to do is visit the webpages that the European Commission devotes to this theme, and that show the action plan of the circular economy package for the current year, 2018, as well as the initiatives in place for promoting the circular economy among a wide range of stakeholders. And this is how it will be in the years to come. Through its ambitious plan for monitoring innovation policies and processes in various economic sectors and in all of the Member States, the European Commission reveals its regulatory talent and its ability to incorporate ideas that, because of the public impact that gave rise to them, need to be duly framed and protected. The environment and the climate may be subject to the risk of catastrophes, but the circular economy has already earned the status of a powerful antidote for preventing them, or at least for lessening their effects.